The preparation of spherical metal powders using the high-temperature remelting spheroidization technology. (1st February 2021) - Bao, Qipeng; Yang, Yiru; Wen, Xiaochun; Guo, Lei; Guo, Zhancheng
Abstract: In this paper, a novel technology to prepare spherical metal powder was proposed. Several spherical metal powders were fabricated successfully by using the high-temperature remelting spheroidization (HRS) technology. Among these powders, thorough research on copper powder spheroidization was conducted. The influence of feed rate and temperature on the properties of as-prepared HRS copper powder was investigated. The particle morphology, particle size distribution, oxygen content, bulk density, fluidity and spheroidization rate of copper powder were characterized. The results showed some unique advantages of the HRS technology in the preparation of spherical metal powders. When the temperature was 1623 K, the particles of HRS copper powder were perfect spheres with smooth surfaces and fully dense with no pores inside. The HRS technology can effectively avoid the defects in conventional methods such as satellite particle and hollow particle. The spheroidization rate of HRS copper powder was nearly 100%. The fluidity of HRS copper powder was 11.4 s/50 g, significantly increased compared to the 56.1 s/50 g of the raw powder. Regarding the settling process and heat exchange behavior of metal particles, we developed the HRS process analytical model. HRS technology is a promising method to prepare high-quality metal powder. Graphical abstract: Unlabelled Image Highlights: Several high-quality spherical metal powders were prepared using the high-temperature remelting spheroidization technology. The particle settlement and heat exchange models were developed to predict the spheroidization process. The quality of spheroidized copper powder improved with the increase of temperature, until complete spheroidization